The influence of stress, income status, and expenditures on families in economic crisis. - Alkhiary, Adnan Mohammed (Kansas State University, 2011)
The purpose of this thesis was to examine how financial stressors influence family well-being. The specific thrust of this thesis was to examine if and how family well-being is influenced by financial stressors caused by the current economic crisis through an adaptation of Hills ABC-X Mosel (1949) known as the ABCE-WB Model. The ABC-X Model was adapted first by White (2007) who substituted the X—crisis element with the WB- well-being item. I added a new element to this model known as E—family expenditures. The data used in this thesis were gleaned from research conducted by Knowledge Networks on behalf of the National Center for Family and Marriage Research. The study was titled: Familial Responses to Financial Instability, How the Family Responds to Economic Pressure: A Comparative Study, 2009. In consisted of nationally representative a (multivariate) address the central hypotheses of this weighted a sample of 1,169 respondents. Analyses included simple correlations (bivariate) and hierarchical analyses investigation that explored what was the relation shop between the resources, perceptions, and expenditures a family had available to them in the current economic crisis and their well-being. The results indicate that approximately 22.4% of the variance in well-being could be explained by the elements in the ABCE-WB Model. In addition, there were several important relationships that were revealed between the predictors and the outcome measures individually. Overall, the efficacy and utility of the ABCE-WB Model was upheld by the results. Based on these findings future use of the ABCE-WB Model holds promise.
Keywords: Well-being; Financial crisis; Family; Expenditures; Economics (0501); Economics, Finance (0508); Sociology (0626)